2011
DOI: 10.1111/j.1442-2050.2011.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher importance of interleukin 6 than classic tumor markers (carcinoembryonic antigen and squamous cell cancer antigen) in the diagnosis of esophageal cancer patients

Abstract: It has been suggested that interleukin 6 (IL-6) plays a potential role in the growth and progression of tumors, including esophageal cancer (EC). The aim of the study was to compare clinical significance of serum IL-6 with classic tumor markers - carcinoembryonic antigen (CEA) and squamous cell cancer antigen (SCC-Ag) - in EC patients in relation to its histological types - squamous cell carcinoma of esophagus (ESCC) and adenocarcinoma (AD) of esophagus. The study included 53 EC patients and 90 healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 21 publications
7
38
0
1
Order By: Relevance
“…IL-6 is activated in response to reflux and the IL-6/STAT3 antiapoptotic pathway may underlie the development of dysplasia and tumor (85). Serum IL-6 levels were reported to provide 87% sensitivity and 92% specificity for EAC diagnosis in a recent retrospective study (86). However, the study only compared between healthy and EAC groups.…”
Section: Cancer-related Inflammationmentioning
confidence: 88%
“…IL-6 is activated in response to reflux and the IL-6/STAT3 antiapoptotic pathway may underlie the development of dysplasia and tumor (85). Serum IL-6 levels were reported to provide 87% sensitivity and 92% specificity for EAC diagnosis in a recent retrospective study (86). However, the study only compared between healthy and EAC groups.…”
Section: Cancer-related Inflammationmentioning
confidence: 88%
“…Also, in the L2-IL-1β mouse model of BE/EAC, exposure to bile acids accelerated development of BE and EAC by an IL-6 dependent mechanism, with failure of carcinogenesis in the setting of IL-6 deficiency 15 . In addition, patients with EAC had higher serum levels of IL-6 than normal controls 52 , and increased serum IL-6 was associated with progression from BE to EAC 53 . IL-6 is also one of the primary inflammatory mediators produced by adipose tissue and thus may be important in obesity-related inflammation 54 .…”
Section: Inflammatory Signaling Pathways Promote Cell Proliferation Amentioning
confidence: 95%
“…The univariate log -rank analysis indicated that the histological type of EC (P = 0.017), tumor studies, where serum levels of other inflammatory proteins such as CXCL -12 and its receptor (CXCR -4), CRP, and IL -6 were also significantly higher in EC patients in comparison with controls. [11][12][13] Other authors have revealed that CXCR -2 expression is significantly higher in patients with EC than in healthy individuals. However, these results were obtained using the immunohistochemical method.…”
Section: Methodsmentioning
confidence: 99%
“…The cut -off value of CXCR -2 levels was estimated using the Youden index as 0.72 ng/ml, while for the classic tumor markers (SCC -Ag, 2 ng/ml; CEA, 4 ng/ml) and CRP (5.75 mg/l), the cut -off values were previously established in our department based on the 95th percentile. [11][12][13] DISCUSSION Chemokines and their specific receptors play an important role in tumor growth, angiogenesis, invasion, and metastasis of several malignancies, including EC. The CXCR2 is a member of the G -protein -coupled receptor family.…”
Section: -13mentioning
confidence: 99%